Case Report: A Rare Case of Nasal Forehead Mass in Kimura's Disease - Zhao, He; Cao, Zhi-wei; Gu, Zhao-wei (Frontiers in Surgery, 2021)
BACKGROUND Kimura’s disease is a rheumatic immune disease and head and neck lymph nodes are often involved. A mass occurring in the nasal forehead is rare. Good prognosis after surgical resection by glucocorticoid therapy is more rare. CASE SUMMARY We report the rare case of a nasal forehead mass in a 45-year-old male patient with Kimura’s disease. The patient underwent resection of the mass in October 2018 in a local hospital and the postoperative pathology was unclear. He then underwent a second resection in our department in December 2019 mainly because growth of the mass was affecting his appearance. Postoperative pathology confirmed that the patient had Kimura’s disease, and he accepted systemic treatment with prednisone. We followed the patient for 10 months after surgery. He is now recovering well and continues to be closely monitored during follow-up. CONCLUSION It is rare that the painless mass in the nasal forehead is diagnosed as a Kimura’s disease.After completely resection of the mass and systemic treatment with prednisone, the patient had a good outcome. We provide experience for the treatment of Kimura’s disease in nasal forehead.